TB and HIV induced immunosenescence: where do vaccines play a role? - Singh, Mona; Patel, Bhumika; Seo, Michael; Ahn, Phillip; Wais, Nejma; Shen, Haley; Nakka, SriHarsha; Kishore, Priya; Venketaraman, Vishwanath (Frontiers in Aging, 2024)
This paper tackles the complex interplay between Human Immunodeficiency virus (HIV-1) and Mycobacterium tuberculosis (M. tuberculosis) infections, particularly their contribution to immunosenescence, the age-related decline in immune function. Using the current literature, we discuss the immunological mechanisms behind TB and HIV-induced immunosenescence and critically evaluate the BCG (Bacillus Calmette-Guérin) vaccine's role. Both HIV-1 and M. tuberculosis demonstrably accelerate immunosenescence: M. tuberculosis through DNA modification and heightened inflammation, and HIV-1 through chronic immune activation and T cell production compromise. HIV-1 and M. tuberculosis co-infection further hastens immunosenescence by affecting T cell differentiation, underscoring the need for prevention and treatment. Furthermore, the use of the BCG tuberculosis vaccine is contraindicated in patients who are HIV positive and there is a lack of investigation regarding the use of this vaccine in patients who develop HIV co-infection with possible immunosenescence. As HIV does not currently have a vaccine, we focus our review more so on the BCG vaccine response as a result of immunosenescence. We found that there are overall limitations with the BCG vaccine, one of which is that it cannot necessarily prevent reoccurance of infection due to effects of immunosenescence or protect the elderly due to this reason. Overall, there is conflicting evidence to show the vaccine's usage due to factors involving its production and administration. Further research into developing a vaccine for HIV and improving the BCG vaccine is warranted to expand scientific understanding for public health and beyond.